Demographic determinants of women’s fertility decision / Rohana Kamaruddin - Kamaruddin, Rohana (Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2016)
Malaysia is an interesting country to study despite a dramatic change in demographic and socioeconomic development. The division of socio-economics among the three ethnicities was influenced by the British colonization, until its independence in 1957. This paper develops an empirical model to investigate the principal determinants of fertility in Malaysia employing panel data extracted from census data from Minnesota Population Centre, Integrated Public Use Microdata Series, International, which was provided by Department of Statistics Malaysia. The analyses were based on proxy of four demographical effects: marital status, age, ethnicity and location. The analyses employ binary model using the dependent variable as 0 (no children) and 1 (with children). The results obtained in this study showed that Malaysian women prefer to have children between the age of 30 to 44. As in the case of ethnicity, only two ethnic groups were significant, with higher probability among Malays at 19 percent and second among Indians at 13 percent. The last variable on location was significant, which indicates that urban Malaysians prefer not to have more children at a probability of 8.9 percent. Consequently, these results demonstrate that women’s preference for children are associated with age, marital status and ethnicity.